Мигрень - Григорова, И.А.; Лещенко, К.А. (Международный медицинский журнал, 2003)
Приведены эпидемиологические характеристики мигрени, освещены ее патогенез и клиника, включая клинические особенности отдельных форм мигрени, а также дифференциальная диагностика. Описаны методы лечения и профилактика приступов заболевания. Epidemiological characteristics of migraine are reported, the pathogenesis and clinical picture of the disease including clinical characteristics of some forms of migraine as well as differential diagnosis of the disease are highlighted. The methods of treatment and prevention of the attacks are described.